An Acoustic Study on the Pronunciation of Vowel Sounds in Spanish, Italian, and French Languages by Mongolian Learner - Sangidkhorloo, Bulgantamir; Bazarjav, Purevsuren; Ganzorig, Bat-Uchral; Lkhagvasuren, Oyu-Erdene (Mongolian Journal of Applied Linguistics, 2023)
This article presents the results of the experimental phonetic study on the pronunciation of vowel sounds in Spanish, Italian and French languages of Mongolian students from the A1 level program at the National University of Mongolia. The study responded to the researchers’ concern to find out which the pronunciation of the vowel sounds of the tree foreign languages by Mongolian students was measured and analyzed using the Praat program. The results of the quantitative research were compared with the standard pronunciation parameters of the native speakers of the respective languages. The results of the study show that the phonetic characteristics of the learner’s mother tongue influence the way of pronunciation of a foreign language. The study shows that practice focused on the phonetic characteristics of the foreign language needed, taking into account the language learning habits and the characteristics of the student’s articulation activities in order to obtain the correct way of pronunciation of sounds of foreign languages. Therefore, it is important not to neglect phonetic content in the teaching methods and materials, and there is a need to increase phonetics and pronunciation exercises in seminars and practice classes. Монгол суралцагчдын испани, итали, франц хэлний эгшиг авианы дуудлагын туршилт судалгаа Хураангуй: МУИС-ийн гадаад хэлний хөтөлбөрийн испани, итали, франц хэлийг А1 түвшинд сурч буй 60 монгол суралцагчийн эгшиг авианы дуудлагын туршилт авиа зүйн судалгааны үр дүнг энэ өгүүлэлд тусгав. Монгол суралцагч гадаад хэлний авиаг хэрхэн дуудаж байгааг Праат программ ашиглан тодорхойлж, тоон судалгааны үр дүнг эх хэлтний жишиг дуудлагын үзүүлэлттэй харьцуулж, дүн шинжилгээ хийв. Судалгааны үр дүн эх хэлтний жишиг дуудлагын үзүүлэлтээс зөрүүтэй байгаа нь суралцагчдын төрөлх хэлний авианы өгүүлүүрийн онцлог гадаад хэлээр зөв дуудахад нөлөөлдөг нь батлагдсан. Судалгааны үр дүн гадаад хэлний зөв дуудлагыг хэвшүүлэхийн тулд авиа зүйн онцлог шинж, тухайн суралцагчийн хэл сурах дадал, өгүүлүүрийн онцлогийг харгалзан нэмэлт дадлага хийлгэх хэрэгцээ байгааг харуулж байна. Тиймээс гадаад хэл сурах, сургах арга зүй, сургалтын хэрэглэгдэхүүнд авиа зүйн агуулгыг орхигдуулахгүй байх нь чухал бөгөөд семинар, дадлагын хичээлээр хийх авиа, дуудлагын дасгалыг нэмэгдүүлэх шаардлагатай байна. Түлхүүр үг: авиа зүй, туршилтын арга, дуудлага, эгшиг авиа, монгол, испани, итали, франц.